Pandangan Dunia Karismatik-Religius Dalam Babad Dipanegara: Kesadaran Kolektif Dalam Konteks Krisis Moral Kontemporer - Delta Viola Abna Syalila; Prima Sulistya Putri (Universitas Negeri Surabaya, 2026)
This article explores the charismatic-religious worldview in Babad Dipanegara as a reflection of the collective consciousness of the Javanese religious-priyayi class during the colonial era, and its relevance to today’s moral leadership crisis. Employing Lucien Goldmann’s genetic structuralism approach, the study analyses the representation of spiritually, moral exemplarity, moral legitimacy, and social solidarity embodied in the figure of Prince Dipanegara. The primary data source is the Babad Dipanegara manuscript in Javanese script, transliterated and philologically examined to ensure accurate interpretation. The findings reveal Dipanegara as an alternative leader who combines political leadership with spiritual guidance. The charismatic-religious leadership values embedded in the text demonstrate as structural homology with the current crisis of leadership integrity in Indonesia. Babad Dipanegara is not merely a historical text but severs as a reflective medium to formulate leadership models rooted in ethics, spirituality, and closeness to the people. This research contributes to the development of leadership studies based on cultural and spiritual values and serves as an ethical reference for shaping future leaders capable of responding to contemporary challenges.